متطلبات أساسية لتقويم وتدعيم المباني الواقعة في المناطق الزلزالية تقنيات التدعيم - حويجة بسام (Latakia University Journal -Engineering Sciences Series, 2019)
إن الأبنية القائمة في مناطق زلزالية خاصة التي لم تستوف متطلبات التصميم الزلزالي واشتراطات الكودات تكون عرضة لجملة من الأضرار الخطيرة. وللحد من الخطر الزلزالي نعمل على إعادة تأهيل المباني القائمة, إذ تتم تقويتها و تدعيمها بهدف زيادة قدرة تحملها للأفعال الزلزالية. وإنّ عملية تقويم المنشآت القائمة لمقاومة الزلازل من خلال تحديد قدرتها الفعلية وبيان العيوب و النواقص أمر هام وضروري لتحديد أسلوب و تقنية إعادة التأهيل. في الواقع، يهدف تقويم وتأهيل المباني والمنشآت القائمة لمقاومة الأفعال الزلزالية إلى تجنب الانهيار الشامل أو الجزئي بما يحفظ السلامة ويخفف من الأضرار في العناصر الإنشائية و غير الإنشائية أثناء وبعد الزلزال. نبين، في هذا البحث، شرحاً لمفهوم فلسفة التصميم الزلزالي, وكذلك أسس عملية التقويم الزلزالي، لنصل إلى عرض طرائق التدعيم المقاوم للزلازل و توضيح التقنيات المستخدمة في تقوية المباني و المنشآت الهندسية الواقعة في مناطق زلزالية. Past earthquakes have emphasized the vulnerability of existing structures which did not satisfy modern seismic design requirements and current engineering standards even though they may have been properly designed and constructed according to earlier codes. Many existing buildings may be inadequate and pose severe risk during seismic events. To mitigate the seismic hazard, existing building should be rehabilitated. The rehabilitation measures to upgrade the capacity of these structures can be performed at some point in their useful lives. The evaluation of the seismic capacity of existing buildings and their deficiencies is essential for the design of a rehabilitation technique. The aim of the evaluation and rehabilitation systems is either for collapse prevention to ensure safety of the occupants or to control the damage to ensure the continuity of operation during and after earthquakes. In this paper, the seismic design, as well as evaluation and rehabilitation process are presented, and the suitability of different techniques for various evaluation systems and rehabilitation strategies are reviewed.